Do Wall Street Landlords Undermine Renters' Welfare?. (18th March 2022) - Gurun, Umit G; Wu, Jiabin; Xiao, Steven Chong; Xiao, Serena Wenjing
Abstract: We examine the recent rise of institutional investment in the single-family home rental market and its implications for renters' welfare. Using institutional mergers to identify local exogenous variation in institutional landlords' scale and market share, we show that rents increase in neighborhoods where both merging firms owned properties (i.e., overlapped neighborhoods) relative to other nonoverlapped neighborhoods. Meanwhile, the crime rate also significantly decreases in overlapped neighborhoods after mergers. Our findings suggest that while institutional landlords leverage their market power to extract greater surplus from renters, they also improve the quality of rental services by enhancing neighborhood safety. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.